Analysis of the Effect of the Age of Postpaid Single-Phase kWh-meters on Measurement Accuracy - Rizal Hidayat Syahputra; Ujang Wiharja; Abdul Kodir Al Bahar (Evolution in Electrical and Electronic Engineering, 2026)
The background of this research stems from the need to ensure that the age of single-phase post-paid kWh meters significantly influences consumer electricity consumption. The accuracy of kWh meter measurements in recording electrical energy usage is a critical factor for PT. PLN (Perusahaan Listrik Negara) is to provide satisfactory service to customers in Indonesia while ensuring no party is disadvantaged. To achieve this objective, routine inspections are conducted on customer kWh meters, particularly those installed beyond the standard limit of 10 years or that exhibit an error deviation exceeding 5%. Testing results from 10 selected customers revealed that 6 customers fell into the normal category with inspection results below 5%, while 4 customers fell into the normal category with results exceeding 5%. The impact of a kWh meter age exceeding the standard limit is a loss for PLN and a gain for the customer if the deviation is "Negative (-)"; in such cases, the customer effectively pays less than the energy consumed. Conversely, it results in a loss for the customer and a gain for PLN if the error deviation is "Positive (+)", requiring PLN to compensate for the energy surplus paid for but not consumed. Therefore, consistent monitoring by PT. PLN as the producer and customer awareness as consumers are essential for maintaining kWh meters to minimise measurement inaccuracies.